2006
DOI: 10.1002/pola.21375
|View full text |Cite
|
Sign up to set email alerts
|

Selective preparation of poly(p‐oxybenzoyl) by using fractional polycondensation

Abstract: Selective preparation of poly(p‐oxybenzoyl) (POB) in the copolymerization system of p‐acetoxybenzoic acid (p‐ABA) and m‐acetoxybenzoic acid (m‐ABA) was examined by using reaction‐induced crystallization of oligomers. Polymer crystals mainly composed of p‐oxybenzoyl moiety were precipitated when the content of m‐ABA in the feed was 30 mol %. The formation of the polymer crystals was attributed to both the reactivity of monomer and the phase‐separation behavior of oligomer. Reactivity of p‐ABA was twice higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Although the yield of the precipitates at χ f of 70 mol % under shearing was only 6.8%, the precipitates were obtained under shearing with the yield of 16.3–47.0% at other χ f values. It has been reported that the yield of the precipitates generally decreases in the middle range of the χ f vales owing to the higher solubility of co‐oligomers . Correspondingly, the yields in these polymerizations became lower at χ f of 50–70 mol % whether the shearing was applied or not.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the yield of the precipitates at χ f of 70 mol % under shearing was only 6.8%, the precipitates were obtained under shearing with the yield of 16.3–47.0% at other χ f values. It has been reported that the yield of the precipitates generally decreases in the middle range of the χ f vales owing to the higher solubility of co‐oligomers . Correspondingly, the yields in these polymerizations became lower at χ f of 50–70 mol % whether the shearing was applied or not.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, the heterogeneous polycondensation which is the polymerization performed in multiple phases such as a solution phase and a solid phase has been developed for the precise control of not only the primary polymer structures but also their higher‐ordered structures. The heterogeneous polycondensation containing the reaction‐induced phase separation had provided sequence control of whiskers, dual self‐assemble polycondensation, and fractional polycondensation . Among them, the fractional polycondensation which is the polymerization to synthesize homopolymers chemoselectively as precipitates in the copolymerization system has a potential to control the composition of copolymers, and the composition control of aromatic copolyesters had been studied by using hydrodynamically induced phase separation during solution polymerization of p ‐acetoxybenzoic acid and m ‐acetoxybenzoic acid .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the fractional polycondensation has been revealed on the basis of this phase diagram as follows6–8; p ‐OB homo‐oligomers are more rapidly formed in the solution than co‐oligomers due to the difference in the reactivity of monomers. When the molecular weight of the p ‐OB homo‐oligomers exceeds a critical value, they are precipitated via crystallization to form crystals at the early stage in the polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Precise control of polycondensation is of great importance to create new polymer materials from the academic and industrial aspects. Many attractive polycondensation methods have been developed so far, including synthesis of sequence‐defined polymers,1 condensative chain polymerization,2 solid‐state polycondensation,3 nucleation‐elongation polymerization,4 nonstoichiometric polycondensation,5 and fractional polycondensation 6–8. Fractional polycondensation, which is one of the precise polycondensations, was reported as the polymerization proceeding by selecting certain monomers in the copolymerization system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation